Growth and Poverty in India: The Current Debate - V. Bijukumar
The relationship between economic growth and poverty is a much debated theme in Indian development. Such relationship time and again assumed significance in the larger context of democracy and the demand for social justice. But India stands the most inegalitarian society in the world despite constitutional provisions put into address various types of inequality. Right based approach to poverty reduction through food security and the realisation of inclusive growth remain as a distant dream when growth does not address issues of poverty, social justice and inclusiveness. This paper attempts to analyse the perpetual contradictions in poverty estimate and efforts for poverty reduction in India.